Nanomaterial-based detection of circulating tumor cells and circulating cancer stem cells for cancer immunotherapy - Yeochan Yun; Seewoo Kim; Sang-Nam Lee; Hyeon-Yeol Cho; Jeong-Woo Choi (Nano Convergence)
Abstract Nanomaterials have emerged as transformative tools for detecting circulating tumor cells (CTCs) and circulating cancer stem cells (CCSCs), significantly enhancing cancer diagnostics and immunotherapy. Nanomaterials, including those composed of gold, magnetic materials, and silica, have enhanced the sensitivity, specificity, and efficiency of isolating these rare cells from blood. These developments are of paramount importance for the early detection of cancer and for providing real-time insights into metastasis and treatment resistance, which are essential for the development of personalized immunotherapies. The combination of nanomaterial-based platforms with phenotyping techniques, such as Raman spectroscopy and microfluidics, enables researchers to enhance immunotherapy protocols targeting specific CTC and CCSC markers. Nanomaterials also facilitate the targeted delivery of immunotherapeutic agents, including immune checkpoint inhibitors and therapeutic antibodies, directly to tumor cells. This synergistic approach has the potential to enhance therapeutic efficacy and mitigate the risk of metastasis and relapse. In conclusion, this review critically examines the use of nanomaterial-driven detection systems for detecting CTCs and CCSCs, their application in immunotherapy, and suggests future directions, highlighting their potential to transform the integration of diagnostics and treatment, thereby paving the way for more precise and personalized cancer therapies. Graphical Abstract